Two cases of dizygotic triplet pregnancy following conventional in vitro fertilization - Furugori, Kazunori (Reprod Med Biol, 2003)
The mechanism of monozygotic multifetal pregnancy and its association with assisted reproductive technology are uncertain. This report presents two cases of dizygotic triplet pregnancy after the transfer of three embryos in utero. The incidence of monozygotic twinning following assisted conception procedures is higher than in the general population. Zonal manipulation may be a major factor in the increased incidence of monozygotic twinning. As both cases followed the conventional in vitro fertilization (IVF), the reason for these monozygotic twinnings might be because of the changes in the zona pellucida in in vitro conditions. In one case, fetuses developed into severe twin‐to‐twin transfusion syndrome (TTTS), resulting in one intrauterine fetal death at 26 weeks gestation. (Reprod Med Biol 2003; 2: 41–44)